Evaluation of advanced curve speed warning system to prevent fire truck rollover crashes. (December 2022) - Simeonov, Peter; Nimbarte, Ashish; Hsiao, Hongwei; Current, Richard; Ammons, Douglas; Choi, Hee-Sun; Rahman, Md Mahmudur; Weaver, Darlene
Highlights: Fire tankers are at increased risk of rollover during emergency response driving. Curve speed warning system (CSWS) was evaluated in a simulator to prevent rollovers. The CSWS issued preemptive warnings but did not reduce the rollover crash events. Analysis of the simulated rollover crashes revealed directions for CSWS improvement. The knowledge generated by this study may be useful for CSWS system designers. Abstract: Introduction: A disproportionately high number of deadly crash-incidents involve fire-tanker rollovers during emergency response driving. Most of these rollover incidents occur at dangerous horizontal curves ("curves") due to unsafe speed. This study examined the effects of a curve speed warning system (CSWS) on fire tanker drivers' emergency response behavior to develop system improvement suggestions. Method: Twenty-four firefighters participated in driving tests using a simulator. A fire tanker model, carrying a full tank of water, was used in emergency driving tests performed with and without CSWS. The CSWS was designed using the algorithm for passenger vehicles with a few initial modifications considering the unique requirements of heavy fire tanker and emergency driving. Results: The results indicated that the CSWS was effective in issuing preemptive warnings when the drivers were approaching curves with unsafe speed during emergency response. Warnings occurred more frequently at curves with smaller radius. Although the CSWS improved driving performance, it did not significantly reduce the number of rollover events. A detailed analysis of the rollover events provided suggestions for improvement of CSWS algorithms. Conclusions: To further improve the CSWS algorithm, the following may be considered: including increased safety speed margin below the rollover critical speed, moving the speed warning trigger from the curve apex to the curve entry point, extending the safe speed-control zone to cover the entire curve, and employing artificial intelligence to accommodate individual driving styles. Practical Applications: Fire tankers continue to be at increased risk of rollover during emergency response due to unsafe negotiation of dangerous curves. Development and use of advanced driver assist systems such as CSWS evaluated in this study may be an effective strategy to prevent deadly rollover crash-incidents. The knowledge generated by this study will be useful for system designers to improve the CSWS specifically designed for heavy emergency vehicles.